Developmental Plasticity in Primate Coordinated Song: Parallels and Divergences With Duetting Songbirds - Adret, Patrice (Frontiers in Ecology and Evolution, 2022)
Homeothermic animals (birds and mammals) are prime model systems for investigating the developmental plasticity and neural mechanisms of vocal duetting, a cooperative acoustic signal that prevails in family-living and pair-bonded species including humans. This review focuses on the nature of this trait and its nurturing during ontogeny and extending into adulthood. I begin by outlining the underpinning concepts of duet codes and pair-specific answering rules as used by birds to develop their learned coordinated song, driven by a complex interaction between self-generated and socially mediated auditory feedback. The more tractable avian model of duetting helps identify research gaps in singing primates that also use duetting as a type of intraspecific vocal interaction. Nevertheless, it has become clear that primate coordinated song—whether overlapping or antiphonal—is subject to some degree of vocal flexibility. This is reflected in the ability of lesser apes, titi monkeys, tarsiers, and lemurs to adjust the structure and timing of their calls through 1) social influence, 2) coordinated duetting both before and after mating, 3) the repair of vocal mistakes, 4) the production of heterosexual song early in life, 5) vocal accommodation in call rhythm, 6) conditioning, and 7) innovation. Furthermore, experimental work on the neural underpinnings of avian and mammalian antiphonal duets point to a hierarchical (cortico-subcortical) control mechanism that regulates, via inhibition, the temporal segregation of rapid vocal exchanges. I discuss some weaknesses in this growing field of research and highlight prospective avenues for future investigation.